Induksi Nanobubbles (NBs) untuk Pertumbuhan Anggrek Dendrobium Imelda Marina Masagung X Bumi Menangis - Rahayu, Tintrim; Jayanti, Gatra Ervi; Hayati, Ari (Metamorfosa: Journal of Biological Sciences, 2023)
Nanobubbles (NBs), nanotechnology has been applied in several fields, such as health, waste management, agriculture, and others. This nanotechnology utilizes the gas in the bubbles, making it easier for the gas to enter the cell. This study aimed to determine the effect of O 2 , CO 2 , N 2 , H 2 , and O 3 gases in NBs on the growth of the Dendrobium Imelda Marina Masagung ´  Bumi Menangis orchid. The method used was to provide fertilizer and NBs treatment to Dendrobium orchids for six weeks with observations every one week. The data obtained were analyzed by two-way ANOVA and further tested post hoc tests with Ptukey <0.05. The results showed significant differences in stem diameter and orchid plant height. The orchid stem diameter was more significant with the NBs treatment than the fertilizer and control treatments. Orchid plants with NBs treatment were higher than those with fertilizer and control treatments. The appearance of new shoots and roots also indicates plant growth. Orchid leaf colour with fertilizer and NBs treatment changed from the Yellow-Green Group (144) to the Green Group (143), except for the control. Leaves colour affects the process of photosynthesis, the green colour will carry out photosynthesis better than Green-Yellow leaves. This affects plant growth in Dendrobium Imelda Marina Masagung ´  Bumi Menangis orchid. NBs enlarge the stem, increase the height and make the leaves green.